Inequality, Family Processes, and Health in the "New" Rural America. (August 2013) - Burton, Linda M.; Lichter, Daniel T.; Baker, Regina S.; Eason, John M.
Rural America is commonly viewed as a repository of virtuous and patriotic values, deeply rooted in a proud immigrant history of farmers and industrious working-class White ethnics from northern Europe. These views are not always consistent with the population and socioeconomic realities of rural terrains. Exceptions to these stereotypes are self-evident among large poor racial/ethnic minorities residing in rural ghettos in the "dirty" South and among poor Whites living in remote, mountainous areas of Appalachia. For these disadvantaged populations, sociocultural and economic isolation, a lack of quality education, too few jobs, and poor health have taken a human toll, generation after generation. Moreover, the past several decades have brought dramatic shifts in the spatial distribution and magnitude of poverty in these areas. And, America's persistent racial inequalities have continued to fester as rural communities become home to urban-origin racial minority migrants and immigrants from Mexico and Latin America. As a result, the face of rural America has changed, quite literally. In this article, we address the primary question these changes pose: How will shifting inequalities anchored in poverty and race shape health disparities in a "new" rural America? Guided by fundamental cause theory, we explore the scope and sources of poverty and race inequalities in rural America, how patterns in these inequalities are transduced within families, and what these inequalities mean for the future of health disparities within and across rural U.S. terrains. Our goal is to review and interrogate the extant literature on this topic with the intent of offering recommendations for future research.